2015
DOI: 10.1039/c4ra15446k
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of carbon nanotube–cobalt ferrite nanocomposites for the adsorption of rhodamine B from aqueous solutions

Abstract: The efficiency of adsorption of rhodamine B (RhB) from aqueous solution was investigated through a series of batch experiments by using cobalt ferrite nanoparticles (CoFe 2 O 4 ), acid-functionalized multiwalled carbon nanotubes (MWCNT-COOH) and carbon nanotube-cobalt ferrite nanocomposites. The adsorption capacity was evaluated as a function of pH, contact time, adsorbent dose, dye concentration and temperature. The effect of increasing the percentage of MWCNT-COOH in the nanocomposites was also studied. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 71 publications
3
62
1
Order By: Relevance
“…The shorter the equilibrium time, the better the adsorbent. The equilibrium time of 5 min reported in this work is far lesser than those reported for carbon nanotubecobalt ferrite nanocomposites (equilibrium time = 6 h) used for removal of RhB in aqueous solution [57], implying that the GONS has a better affinity for RhB compared to the composites of carbon nanotube-cobalt ferrites. Zhou et al [37] have also demonstrated that GO is a better adsorbent than Fe l O ¡ /GO composites, in terms of enhanced adsorption capacity of former, due to replacement of active adsorption sites on GO by Fe l O ¡ nanoparticles of Fe l O ¡ /GO.…”
Section: Effect Of Contact Time and Adsorption Kineticscontrasting
confidence: 60%
“…The shorter the equilibrium time, the better the adsorbent. The equilibrium time of 5 min reported in this work is far lesser than those reported for carbon nanotubecobalt ferrite nanocomposites (equilibrium time = 6 h) used for removal of RhB in aqueous solution [57], implying that the GONS has a better affinity for RhB compared to the composites of carbon nanotube-cobalt ferrites. Zhou et al [37] have also demonstrated that GO is a better adsorbent than Fe l O ¡ /GO composites, in terms of enhanced adsorption capacity of former, due to replacement of active adsorption sites on GO by Fe l O ¡ nanoparticles of Fe l O ¡ /GO.…”
Section: Effect Of Contact Time and Adsorption Kineticscontrasting
confidence: 60%
“…This fact suggests negative charge exists on the surface of MFe 2 O 4 /CNTs, promoting cationic adsorption during the adsorption process. 24,58 In addition, log K ow and log K oc of BZF are 4.25 and 1.0 at pH ¼ 7.4, 59 respectively, indicating that BZF has a high tendency to sorb onto the organic material. For practical application, the water matrix such as pH and organic carbon content, may have signicant effects on BZF adsorption.…”
Section: Adsorption Mechanismmentioning
confidence: 99%
“…Among the various magnetic materials, ferrites exhibit high efficiency and are environmentally friendly. 23,24 Some ferrites, such as MnFe 2 O 4 and CoFe 2 O 4 , are excellent adsorbents, and their magnetic properties ensure that they can be magnetically separated. 25 Furthermore, synergistic adsorptive removal of heavy metals from aqueous solution has been reported for combined application of ferrite and carbon materials.…”
Section: Introductionmentioning
confidence: 99%
“…As seen from Figure 9 (d), AY17 removal efficiency fell from 78% to 36% as the initial AY17 concentration increased from 2 to 120 mg L -1 at 293 K. The reduction of dye removal efficiency may be due to the fact that at the higher initial dye concentration, the total exiting adsorptive sites are confined as a result of the fixed amount of adsorbent. Hence, saturation of the adsorptive sites of the adsorbent with dye anions may occur as the adsorption process continues, 28 leading to a decrease in dye removal with an increase in dye concentration. Furthermore, from Figure 9 (d), it is observed that the removal efficiency improved from 36% at 293 K to 61% at 323 K at an initial concentration of 120 mg L -1 .…”
Section: Effect Of Initial Ay17 Dye Concentrationmentioning
confidence: 99%